Intersectional examination of transgender women in South Korea: a case study of the dismissal of the first transgender officer by the Ministry of National Defense - Park, Jungman; LIU, Jianwen (International Journal of Korean Humanities and Social Sciences, 2023)
This paper presents an intersectional examination of transgender women in South Korea, focusing on the dismissal of the first transgender officer, Hee-soo Byun (who committed suicide later after the dismissal), by the Ministry of National Defense in 2021. Drawing on the principles of Korean feminism and the third-wave feminist emphasis on intersectionality, the study examines the intersecting factors of gender identity, military service, and institutional policies that contribute to the marginalization and mistreatment of transgender individuals. By investigating the multifaceted challenges experienced by transgender women in South Korea, this paper highlights the complex dynamics of discrimination, taking into account the unique cultural and socio-political context of Korean society. This article aims to contribute to the existing body of knowledge on transgender rights, gender equality, and feminist activism in South Korea, providing insights to inform future discussions, policies, and actions aimed at promoting inclusivity and equal opportunities for transgender individuals within the context of military service and beyond.